Overt and Null pronominal subject in the beginning of the 21st century (and their relation to the null object in BP) - Othero, Gabriel de Avila (2019)
In this article, we investigate the occurrence of null and overt pronominal subjects in two recent theater plays. Our investigations present two main goals: (i) to continue, so to speak, the pioneering work of Duarte (1993, 1995) on overt pronominal subjects in BP; and (ii) to test the semantic gender hypothesis genre (by Creus & Menuzzi, 2004), applying it to the analysis of pronominal subjects in our corpus. We confirmed the hypothesis anticipated in Duarte (1993, 1995) that BP favors overt pronominal subjects (in the fashion of a -pro-drop language). And we also point to a direction not yet investigated in the literature: overt pronominal subjects preferentially refer to referents or antecedents with semantic gender, which suggests that this feature may indeed be a relevant factor favoring the overt pronoun in BP, both for the direct anaphoric object (as recent works in the literature show), and for the pronominal subject (as we outline here).